2021
DOI: 10.1177/08862605211042871
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Maternal Self-efficacy in the Link Between Childhood Maltreatment and Maternal Stress During Transition to Motherhood

Abstract: The transition to motherhood is a significant developmental milestone in many women’s lives. This transitional period may be more stressful for women with a history of childhood maltreatment (CM) than for women without such a history. This study tested whether parental self-efficacy (PSE) accounts for the link between CM and parental stress in mothers transitioning to motherhood. The study used a convenience sample of 1,306 first-time mothers of children aged two years or younger. Mothers filled out online sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 89 publications
0
7
0
1
Order By: Relevance
“…The results showed that parental depression was positively associated with parenting stress, which was consistent with previous studies ( 56 ). Individuals with depression may have less self-efficacy ( 57 ), which may contribute to high levels of parenting stress. The results also showed that parental depression was positively associated with child maltreatment, which was consistent with previous studies ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that parental depression was positively associated with parenting stress, which was consistent with previous studies ( 56 ). Individuals with depression may have less self-efficacy ( 57 ), which may contribute to high levels of parenting stress. The results also showed that parental depression was positively associated with child maltreatment, which was consistent with previous studies ( 58 , 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the results showed that parenting stress and child maltreatment progressively mediated the relationships between parental depression and child internalizing and externalizing problems, which suggested that parental depression influenced child internalizing and externalizing problems via the combination of parenting stress and child maltreatment. Individuals with depression may have low levels of self-efficacy ( 57 ) and attention biases in negative information ( 29 ), which may contribute to high levels of parenting stress, and these high levels of parenting stress may increase the risk of child maltreatment, which, in turn, contributes to high levels of child internalizing and externalizing problems. The results confirm the assumptions offered by the model of depressed mothers and maladaptation of children and those proposed by the family system theory, and raises the importance of exploring parental depression.…”
Section: Discussionmentioning
confidence: 99%
“…Women enter motherhood with various personal histories of development and many intrapersonal enduring characteristics primarily as a result of their developmental histories (Belsky, 1984). Such histories and characteristics, albeit as relatively distal factors, considerably affect maternal adaptation to the transition to parenthood as well as their early parenting processes (e.g., Barrett & Fleming, 2011; Belsky & Jaffee, 2006; Bentley & Zamir, 2021; Christie et al, 2017; Kerr & Capaldi, 2019; Savage et al, 2019; Yıldız Inanıcı et al, 2021). Due to the focus of our review, we particularly emphasize the key implications of mothers’ own experiences of early emotion-related parenting, especially in distress contexts, in their families of origin for the formation and development of maternal self-regulatory capacities and adult attachment style/representations.…”
Section: Review Of Existing Empirical Research That Is Relevant To Th...mentioning
confidence: 99%
“…The transition to motherhood is an important developmental milestone in many women’s lives ( 1 ). Many pregnant women report that they are more aware of judgement from others and experience a burden of complying with very limited understandings of motherhood, which can adversely affect their mental health ( 2 ).…”
Section: Introductionmentioning
confidence: 99%